European Union expansion and migration - Martin Kahanec; Lucia Kureková (Institute for the Study of Labor (IZA), 2011)
This paper concisely reviews what we know about the experience of an enlarging European Union with free movement of workers within its borders. We focus on the two most recent, Eastern, enlargement waves of 2004 and 2007. We first assess the actual migration flows following the enlargements against the pre-enlargement expectations and perceptions. We then review the effects of these flows on the labor markets of receiving as well as sending countries. We conclude that the available evidence does not indicate negative effects on the receiving countries' labor markets or welfare systems. From the sending countries' perspective the risks of out-migration lie in skill shortages in affected occupations or sectors as well as the potential (in)stability of their public finances, whereas the potential benefits may materialize through brain circulation. Overall, free mobility can be described as one of the key achievements, and success stories, of European integration.
Keywords: F22; J61; 330; migration; effects of migration; EU enlargement; free movement of workers; EU-Mitgliedschaft; Internationale Wanderung; Arbeitsmigranten; EU-Staaten; EU-Mitgliedschaft